ANALISIS TEKNOLOGI INFORMASI BALANCE SCORECARD DAN ENTERPRISE ARCHITECTURE UNTUK INDUSTRI PARAWISATA PADA HOTEL KARTIKA CHANDRA - Saragih, Hoga; Yesmaya, Violitta (Teknik dan Ilmu Komputer, 2013)
Information technology is employed to allow its users to manage information more quickly and effectively today. Advances in technology at the hospitality industry has evolved over the years. Strategic planning is one way that allows companies or organizations to increase competitive advantages and minimize disadvantages. The development of technology in the hospitality field has resulted in better business processes. This paper aims at producing IT strategic planning for the hospitality industry to support the hotel business processes. The method used in this research is the IT strategic planning framework introduced by John Ward. New applicationsportfolio such as Mobile Web Application, CRM, Knowledge Management System, Information Technology Balance Score Card (ITBSC) and Enterprise Architecture (EA) are proposedby the IT strategic planning at the hospitality industry.Â Keywords: IT strategic planning, tourism, portfolio application